FAKTOR-FAKTOR PENGHAMBAT PENINGKATAN LOAN TO DEPOSIT RATIO (LDR) PERBANKAN DI PROPINSI BALI - I Wayan Sudirman (Journal of Indonesian Economy and Business (JIEB), 2003)
The goals of this research are to examine factors affecting the Loan to Deposit Ratio(LDR) raising which is based on supply and demand, to examine the impact the decline ofLDR to small business credit, to identity the appropriate scheme for the small business and then to make recommendation in optimalizing LDR in Bali’s economy.Based on Slovin approach, the sample size of small business chosen as respondent were100 units. To reach the overall perception, 15 commercial banks (Bank Umum) and 16Secondary Banks (Bank Perkreditan Rakyat/BPR) were selected also as respondents.Multiple regression analysis supported by stepwise regression was used to test factorsaffecting LDR. To examine factors affecting LDR based on demand, the tools used wasdescriptive statistics. This is expected to support regression analysis, especially to makeintegrated decision making.This research finding indicated that, first, actors that simultaneously affected LDR-BPRwere core capital, supplementary capital, saving in other bank, saving interest rate, timedeposit in other bank, time deposit interest rate, fund from society at previous period, credit at previous period, PPAP to PPAPWD ratio and cover guarantee. Partially, there wereseven variables significantly contribute to LDR including supplementary capital, savinginterest rate, time deposit in other bank, time deposit interest rate, credit at previousperiod, PPAP to PPAPWD ratio and cover guarantee.Second, factors that simultaneously affected LDR-BU were cash in other bank, clearingaccount interest rate, saving in other bank, saving interest rate, time deposit in other bank, time deposit interest rate, Bank Indonesia Certificat (SBI), SBI interest rate, fund from society at previous period, invested bank fund, credit at previous period, credit interest rate, PPAP to PPAPWD ratio and cover guarantee. Partially, there were nine variables that significantly contribute to LDR-BU including clearing interest rate, saving in other bank, time deposit interest rate, SBI interest rate, invested bank fund, credit at previous period, credit interest rate, PPAP to PPAPWD ratio and cover guaranteee. Third, an average LDR of BPRs in Bali for the five period (quarterly) was 91, 75% which mean BPR were in healty condition from the liquidity point of view. But, for LDR-BU an average LDR was 46, 23% that indicated less healty conditon. Forth, although BPR in good condition, it can be optimalized through four variables. Fifth, for LDR-BU there were six variables that can be optimalized to increase LDR. Sixth, the low average of LDR-BU from demand side point of view were because of lack of information about the opportunity for small business.Another finding, of this research was that an innovative credit scema for small business isnot based on low rate of credit interest, but the small business need a competitive creditscema.Keywords: Loan Deposit Ratio (LDR); small business; Commercial Bank, Secondary Bank.